Antibiotic consumption monitoring at the Institute of Otorhinolaryngology and Maxillofacial Surgery - Clinical Center of Serbia in 2001-2003 - Kastratović Dragana A.; Đukić Vojko B.; Majstorović Branislava M.; Komrska Jan J.; Gajić Milan M.; Marković Srđan Z. (Vojnosanitetski Pregled)
Background. At the Clinical Center of Serbia (CCS), which includes 21 Institutes and 6 Centers, approximately 10% of the total annual budgetary funds is spent on the drugs. During the studied period, it was estimated that 0.5% of the above amount has been spent at the Institute for Otorhinolaryngology and Maxillofacial surgery (Institute for ORL and MFS), Clinical Center of Serbia. The aim of this study was to find out if these antibiotics had been used rationally by the monitoring of antibiotics in relation to the number of inpatients, and by the 5 most frequent diagnoses. Methods. The authors monitored the tree-year consumption of antibiotics for In hospital treated patients during the period 2001-2003. Data were obtained from the itemized quarterly report on the consumption by the Central Pharmacy of the CCS. Results. The results were statistically analyzed and presented in percentages and Defined Daily Dasages (DDD) for each group of the antibiotics. The results were analyzed in accordance with the World Health Organization Recommendations and the Guidelines. Conclusion. The authors concluded that antibiotics were adequately used at the Institute for ORL and MFS-CCS. The most commonly used antibiotics for grampositive infections were those from the penicillin and cephalosporin groups. According to the international trends and recommendations, the selected therapy was rational and the antibiotics consumption was cut down during the observed three-year period. It was a true confirmation that the recommendations for the rational antibiotics consumption had been fruitful (produced good results).